Body image perception and social support as predictors of psychological distress among third trimester pregnant women in Nigeria - Oluwaseyi Isaiah Olabisi; Eunice Ogunmodede; Simeon Ojo; Oluwafemi Ilori; Deborah T. Esan (BMC, 2024)
Abstract Background Body image perception and social support during pregnancy can impact the psychological distress levels experienced by pregnant women. As a result, the purpose of this study was to examine the relationship between various components of social support and body image perception on psychological distress levels among pregnant women in their third trimester in Nigeria. Method A cross-sectional study was conducted among 246 pregnant women who were in the third trimester and attending selected health care facilities in Ogbomoso, a semiurban city in Oyo State, Nigeria. Body image perception, social support, and psychological distress scales were used to collect the data. Data were analyzed and summarized using descriptive and inferential statistics (ANOVA and multiple regression), with significance set at p < 0.05. Results Regression analysis showed that 44% of the variation in psychological distress among pregnant women was explained by the background variables, marital status, body image perception, appraisal support, tangible support, belonging support, interaction between body image perception and appraisal support, belong support and tangible support. Conclusion Intervention programs focusing on bolstering tangible support, belonging support and appraisal support are recommended at reducing the psychological distress due to body image perception among pregnant women at third trimester.